A smart all-in-one theranostic platform for CT imaging guided tumor microwave thermotherapy based on IL@ZrO2 nanoparticles1. Issue 8 (14th August 2015) - Shi, Haitang; Niu, Meng; Tan, Longfei; Liu, Tianlong; Shao, Haibo; Fu, Changhui; Ren, Xiangling; Ma, Tengchuang; Ren, Jun; Li, Linlin; Liu, Huiyu; Xu, Ke; et al.
<x xml:space="preserve">Abstract</x> This paper develops a simple multifunctional theranostic platform using an IL@ZrO2 nanostructure for CT imaging guided tumor microwave thermotherapy.